(untitled) (Oxford, 1990)
This book offers a unique combination of English, European, feminist, and " new writing " of " Commonwealth " perspectives upon literacr studies from the 1920s to the 1980s. It includes the views of leading critics and theorists such as Marilyn Butler, Frank Kermode, Hélène Cixous, and Edward Said as well as the originating voices of Wole Soyinka, Toni Morrison, Seamus Heany, and Virginia Woolf, and focuses on major critical topics including genre, interpretation, history and criticism, gender, race, and the notion of " Englishness "
Keywords: Criticism,Developing countries,Literature, modern; History,Literature,Occidental influences,History and criticism; 20th century,20th century